Syntheses of 2-substituted 1-amino-4-bromoanthraquinones (bromaminic acid analogues) – precursors for dyes and drugs - Malik, Enas M.; Baqi, Younis; Müller, Christa E. (Beilstein Journal of Organic Chemistry, 2015)
Anthraquinone (AQ) derivatives play a prominent role in medicine and also in textile industry. Bromaminic acid (1-amino-4-bromoanthraquinone-2-sulfonic acid) is an important precursor for obtaining dyes as well as biologically active compounds through the replacement of the C4-bromo substituent with different (ar)alkylamino residues. Here we report methods for the synthesis of bromaminic acid analogues bearing different substituents at the 2-position of the anthraquinone core. 1-Aminoanthraquinone was converted to its 2-hydroxymethyl-substituted derivative which, under different reaction conditions, yielded the corresponding carbaldehyde, carboxylic acid, and nitrile derivatives. The latter was further reacted to obtain 1-amino-2-tetrazolylanthraquinone. Subsequent bromination using bromine in DMF led to the corresponding bromaminic acid derivatives in excellent isolated yields (>90%) and high purities. Alternatively, 1-amino-4-bromo-2-hydroxymethylanthraquinone could be directly converted to the desired 2-substituted bromaminic acid analogues in high yields (85–100%). We additionally report the preparation of bromaminic acid sodium salt and 1-amino-2,4-dibromoanthraquinone directly from 1-aminoanthraquinone in excellent yields (94–100%) and high purities. The synthesized brominated AQs are valuable precursors for the preparation of AQ drugs and dyes.
Keywords: anthraquinone; bromaminic acid; drug synthesis; dyes; intermediates